The Application of Antioxidant in Skin Cancer Research: A Bibliometric Study - Alwi, Luqman; Budiono, Irwan; Azam, Mahalul; Ningrum, Dina Nur Anggraini; Intania, Irena; Budijitno, Selamat; Muhtar, Muhammad Solihuddin (Asian Pacific Journal of Cancer Care, 2025)
Objective: Skin cancer is one of the most common malignancies globally. Considering the potential therapeutic benefits of antioxidants, this study aims to examine the trends and patterns in antioxidant application within skin cancer research over the past three decades. Methods: A bibliometric analysis was conducted on 990 English-language articles published between 1990 and 2025, retrieved from the Scopus database. Data were processed using Bibliometrix (R-based) and VOSviewer to assess publication trends, research productivity, collaboration networks, keyword co-occurrence, and thematic evolution in antioxidant-related skin cancer research. Result: The annual growth rate of publications reached 11.42%, with a sharp rise in output post-2010. The United States and China were the most productive countries, while European countries demonstrated strong international collaboration. Frequently recurring subjects included apoptosis, cancer, oxidative stress, and antioxidants. Co-occurrence analysis identified four major clusters: (1) cell biomolecular mechanisms, (2) drug metabolism, (3) malignancy agents, and (4) pharmacological innovation. Highly cited articles emphasized molecular mechanisms of antioxidants in tumor suppression. Thematic evolution showed a transition from mechanistic studies to translational and clinical research. Conclusion: Antioxidant-related research in skin cancer is rapidly evolving, with increasing global contributions and thematic diversification. This study provides a comprehensive overview of current knowledge and identifies key research gaps, including the underexploration of areas such as DNA repair, tumorigenesis, and lesser-studied antioxidant compounds, as well as the limited translation of mechanistic findings into clinical applications.